History that the libraries count: the particular library Profesor Osni de Medeiros Regis - Vidal, Mariana Jucelia (2019)
This article presents the history of the Professor Osni de Medeiros Regis Library, located at Av. Mauro Ramos, n.1344, in the city of Florianopolis, SC, Brazil. The study reports the history of the library, describing the creation processes, the construction of the physical space, the composition of the collection and the creation of the foundation to maintain the library and provide access to the public. Establishing an analysis of the importance of the library to the florianopolitan community, and describing the types of services the library provides to the community at large. The methodological procedures that guided the construction of the article were bibliographic research, documental research and interviews, enabling to verify the importance of the library for the community and fr the area of library science.